Case study on lightning protection system in term of collection volume method at Faculty of Science Computer and Mathematics in Universiti Teknologi MARA Shah Alam: article - Ibrahim, Nurhafizaturrafizah (Faculty of Electrical Engineering, 2014)
Risk assessment is a process in order to detect potential hazard and analyses the possible occurrences happen towards the building and assets by using the suitable lightning protection system (LPS). The study based on the Faculty Science Computer & Mathematics in order to decrease the risk of breakdown to electric and electronic devices because of lightning strikes. The risk of building will be determined based on Malaysian Standard Lightning Protection System MS 62305, which are divided into four parts. The tolerable risk that will consider to the human life that is 10-5 can be compared with R1 (calculated value from equation). If R1 > RT, the suitable protection measure used in order to decreased risk cause by lightning strikes. The recommended method for this project is Collection Volume Method (CVM). This method had been evaluated and been discussed for any improvement and reliability regarding the risk assessment at respective building.